Comparative characteristics of Lupinus albus L. and Lupinus luteus L. under allelopathic effect of Sorghum halepense L. (Pers.) - Georgieva, Natalia; Nikolova, Ivelina; Marinov-Serafimov, Plamen (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Allelopathic effects of aqueous extracts of Sorghum halepense L. (Pers.) on seed germination and primary seedling growth and development of two lupine species was studied. Lupinus albus and Lupinus luteus showed different levels of susceptibility to the allelopathic effect of weed extracts. Increasing concentrations (1.25, 2.50, 5.00 and 10.00%) of extracts from aboveground and belowground biomass suppressed seed germination of L. luteus from 53.2 to 74.7%. The germination of L. albus seeds was unaffected, except by the highest concentration of 10.00%. Fresh biomass accumulation in the initial germ of L. luteus was inhibited by 3.8-40.3% under the effect of concentrations of 2.50, 5.00 and 10.00%, which made the species susceptible to S. halepense extracts. L. albus was tolerant as it was not found to sustain a significant allelopathic effect of the extracts.